2020
DOI: 10.1093/dote/doaa112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of peroral endoscopic myotomy for achalasia in children: a systematic review and meta-analysis

Abstract: Peroral endoscopic myotomy (POEM) is a novel minimally invasive intervention, which has shown to be effective and safe for treating achalasia in adults. Presently, POEM was also reported to be effective for achalasia in children. So we conducted this study to explore the clinical outcomes of POEM for pediatric achalasia. A systematic literature search in PubMed, Embase, and Cochrane databases was performed, which covered the period from January 2009 to June 2020. Selecting studies and collecting data was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…56 A 2021 systematic review and meta-analysis with a pooled sample of 389 patients reported technical success of 97.4% and clinical success of 93.9 (<1 year), 96.6% (1-3 years), and 95.5% (>3 years). 55 Long-term success of POEM was recently reported by Nabi et al where 94.7% of their patient cohort had clinical success at mean follow up of 68.5 months. 57 In 2019 retrospective study of 17 patients, Nabi et al reported similar clinical success between patients who were treatment naïve and those with history of previous treatments (Nabi2019) demonstrating the utility of POEM in children who have failed previous treatment modalities.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…56 A 2021 systematic review and meta-analysis with a pooled sample of 389 patients reported technical success of 97.4% and clinical success of 93.9 (<1 year), 96.6% (1-3 years), and 95.5% (>3 years). 55 Long-term success of POEM was recently reported by Nabi et al where 94.7% of their patient cohort had clinical success at mean follow up of 68.5 months. 57 In 2019 retrospective study of 17 patients, Nabi et al reported similar clinical success between patients who were treatment naïve and those with history of previous treatments (Nabi2019) demonstrating the utility of POEM in children who have failed previous treatment modalities.…”
Section: Introductionmentioning
confidence: 83%
“…58 The abovementioned studies all reported success rates of >90% despite 21% to 29% of their cohorts having history of prior treatments. [54][55][56][57] Further studies are needed in pediatrics to determine if history of prior treatment(s) affects POEM outcomes.…”
Section: Peroral Endoscopic Myotomy (Poem)mentioning
confidence: 99%
See 2 more Smart Citations
“…After Inoue et al described the first series of patients who received peroral endoscopic myotomy (POEM) in 2010 ( 11 ), POEM became a minimally invasive, rapid recovery, and preferred relatively novel procedure for achalasia in adults ( 12 , 13 ). Multiple studies have also confirmed its efficacy and safety in children and adolescent patients ( 14 21 ). However, the long-term follow-up study in children, notably more than 5 years, is unclear.…”
Section: Introductionmentioning
confidence: 91%